Model-independent measurement of t-channel single top quark production in p(p)over-bar collisions at,root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; Aoki, M.; et al. (Elsevier B.V., 2011)
We present a model-independent measurement of t-channel electroweak production of single top quarks in p collisions at root s = 1.96 TeV. Using 5.4 fb(-1) of integrated luminosity collected by the do detector at the Fermilab Tevatron Collider, and selecting events containing an isolated electron or muon, missing transverse energy and one or two jets originating from the fragmentation of b quarks, we measure a cross section sigma (p (p) over bar -> tqb + X) = 2.90 +/- 0.59 (stat + syst) pb for a top quark mass of 172.5 GeV. The probability of the background to fluctuate and produce a signal as large as the one observed is 1.6 x 10(-8), corresponding to a significance of 5.5 standard deviations. (C) 2011 Elsevier B.V. All rights reserved.